Gender and Climate Change Research : Moving Beyond Transformative Adaptation - Santos, Pablo Romero-Nieva; Holm, Nikolai George Lewis; Olsen, Julia; Hovelsrud, Grete K. (The University of the Arctic Thematic Network (TN) on Geopolitics and Security, 2020)
Publisher's note: The Arctic Yearbook is open access. Readers may download, distribute, photocopy, cite or excerpt this Arctic Yearbook material provided it is properly and fully credited; however, we do not allow commercial use or the making of derivatives. Research on how communities in the Arctic can overcome the challenge of climate change have traditionally employed adaptation frameworks. The ability of these groups to continue thriving in the Arctic is complicated by historical, social, economic, and political complexities - issues thoroughly addressed through the postcolonial feminist concept of transformation. This article critically examines contemporary research on climate and gender, and the extent to which feminist transformative concerns are addressed, thereby challenging systems and promoting power structures that recognize or benefit all segments of society. The article adopts an analytical strategy which combines two parallel instances of critical reflection on climate research, specifically, a systematic literature review of climate and gender studies in the Canadian Arctic, and the results of a round-table workshop of international climate experts and researchers on the state of climate change, adaptation and gender research in the Arctic. The article explores the results of these analyses and distinguishes those strategies that represent a continuation of status-quo power relations and climate adaptation processes from those that account for current economic and socio-political factors. publishedVersion